60 ANOS DEPOIS: UM OLHAR SOBRE AS VARIÁVEIS MAPEADAS NO ESTADO DA ARTE DOS ATLAS LINGUÍSTICOS BRASILEIROS - GUEDES, REGIS JOSE DA CUNHA (Revista de Letras, 2024)
This study aimed to present and discuss the state of the art of Brazilian linguistic atlases, already published, elaborated and the atlases in progress, with the purpose of observing the directions of Brazilian geolinguistics regarding the variables mapped in these atlases, especially since the creation of the National Committee of the ALiB Project (Atlas Linguístico do Brasil) in 1996. This work was based on the theoretical-methodological assumptions of Modern Dialectology, (Cardoso, 2010; 2013), Aguilera (2013), Pluridimensional and Relational Dialectology (Radtke; Thun , 1996) and Geosociolinguistics (Razky, 1998; Guedes, 2017). The methodology used was qualitative and quantitative. Starting from a bibliographic and documentary review, a data collection was carried out from the Plataforma Lattes, Google Scholar and University Repositories on the state of the art of Brazilian linguistic atlases. From the results obtained, it was verified that the creation of the National Committee of the ALiB Project, in 1996, had a large impact, stimulating the production of other linguistic atlases in Brazil. Moreover, the analysis of the methodologies adopted in these linguistic atlases demonstrated that the number of linguistic variables mapped has increased and diversified. Keywords: Linguistic Atlases; Linguistic Variables; Geolinguistics.